ASSESSMENT OF LEARNING STYLE PREFERENCES UTILISING THE VISUAL (V), AUDITORY (A), READ/WRITE (R), AND KINAESTHETIC (K) (VARK) QUESTIONNAIRE: A CROSS-SECTIONAL STUDY - Mishra, Gopabandhu; Dash, Lipsita; Sahoo, Duryodhan; Mohanty, Sujit Kumar (Student's Journal of Health Research Africa, 2024)
Background The learning preferences of medical students are quite diverse. Therefore, to successfully adapt instructional tactics and approaches to meet the requirements of each student and foster a conducive learning environment, educators must be aware of the various learning styles. Therefore, an insightful tool to evaluate learning styles is the VARK instrument, which stands for visual (V), auditory (A), read/write (R), and kinaesthetic (K). The study has been conducted to identify learning style preferences among students of MBBS first year. Materials and methods The study was a cross-sectional study. The research has been conducted for 3 months at Dharanidhar Medical College and Hospital, Keonjhar, Odisha, India. Consent was obtained from the participants before initiation of the study. VARK questionnaire has been provided to the enrolled participants in the form of Google Forms. The student's preferences for different VARK components were examined using descriptive statistics. Results Overall, 160 students participated in the study. Among all the participants, 90 students were male, and the rest 70 were female students. Visual, auditory, read/write and kinaesthetic approaches were present in 08 (17.7%), 05 (11.1%), 03 (6.6%), and 29 (64.4%) of participants respectively in the unimodal approach of learning. Learning styles incorporating visual, aural, read/write, and kinaesthetic methods were shown to differ significantly. Conclusion The results of this study provided considerable support for the usage of blended learning by educators to accommodate a variety of learning preferences and foster learning. Levels of the student learning process have been determined by seeking the preference of different learning styles by the students and with the use of innovative and multimodal teaching methods to make the classroom.